2013
DOI: 10.3109/09593985.2013.862890
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of subjective and motor fatigue in Polio survivors, attending a Postpolio clinic, comparison with healthy controls and an exploration of clinical correlates

Abstract: Motor fatigue has been identified in Polio survivors but was only significantly different in hand grip, using this approach. Pain, fatigue and elevated energy cost of walking negatively influenced quality of life. Motor fatigue was unrelated to subjective fatigue, mobility or quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…In contrast to large muscles, the small muscles of the hand are well suited for clinical studies focusing on (chronic) disease-related changes in neuromuscular function ( Sheean et al, 1997 ; Thomas, 1997 ; de Ruiter et al, 2001 ; Thickbroom et al, 2006 ; Steens et al, 2012 ; Murray et al, 2014 ; Prak et al, 2015 ; Santarnecchi et al, 2015 ; Arnold et al, 2017 ). Previously we examined force decline during sustained maximal contractions with the index finger abductor muscle (the first dorsal interosseous, FDI).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to large muscles, the small muscles of the hand are well suited for clinical studies focusing on (chronic) disease-related changes in neuromuscular function ( Sheean et al, 1997 ; Thomas, 1997 ; de Ruiter et al, 2001 ; Thickbroom et al, 2006 ; Steens et al, 2012 ; Murray et al, 2014 ; Prak et al, 2015 ; Santarnecchi et al, 2015 ; Arnold et al, 2017 ). Previously we examined force decline during sustained maximal contractions with the index finger abductor muscle (the first dorsal interosseous, FDI).…”
Section: Introductionmentioning
confidence: 99%
“…Other impairments such as sleep disturbances, concentration difficulties, memory difficulties, and mood swings are also reported and may be directly or indirectly associated with the prior experience of polio [1,3,6,7]. The new or increased impairments can lead to activity limitations and participation restrictions and thus have an impact on life satisfaction [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that increased disability following LEoPs is associated with decreased life satisfaction compared to healthy persons. 3,7,8 Life satisfaction is related to concepts such as happiness and well-being, and can be described as how a person perceives his or her life situation. 9 The level of satisfaction is affected by the person's expectations with life and thereby reflects how well aspirations and achievements are met.…”
Section: Introductionmentioning
confidence: 99%